Can Suramadu Bridge Reduce International Migration? (Case Study in Bangkalan Regency, East Java Province, Indonesia) - ., Karyadinata; ., CHK; ., M. Pudjihardjo; ., A. Manzilati; ., W. Syafitri (KnE Social Sciences, 2020)
Migration is one way for villagers in Bangkalan District to survive and improve their lives. Availability of employment and differences in the level of wages received in migrant areas are attractive factors, while the condition of villages in terms of physical capital, human capital, financial capital and natural capital which are less than ideal are the driving factors for migrating. This study examines the impact of the Suramadu bridge on the number of villagers migrating internationally using Village Potential data in 2007 and 2017 along with the factors that influence villagers to migrate internationally. Data were analyzed using tobit regression. The existence of the Suramadu bridge was not able to reduce the interest of the population to migrate internationally, instead it even increased the interest of the population to migrate internationally. Before the Suramadu bridge was operational, the existence of rice fields, building area, program credit, non-agricultural business, educational facilities and superior products reduced the interest of villagers to migrate internationally. After the Suramadu bridge operated, the existence of rice fields, building area and skills facilities reduced the interest of villagers to migrate internationally and the presence of poor people in the village increased the interest of residents to migrate. Keywords: Migration, Infrastruktur, Rural, Regional